Emerging Biomarkers for the Diagnosis and Monitoring of Inflammatory Bowel Diseases. Issue 12 (December 2016) - Caire, M. Thure; Strauss, Alexandra T.; Kumar, Ambuj; Brady, Patrick
Abstract : Article first published online 4 November 2016.